The environmental pollutant and carcinogen 3-nitrobenzanthrone and its human metabolite 3-aminobenzanthrone are potent inducers of rat hepatic cytochromes P450 1A1 and -1A2 and NAD(P)H:quinone oxidoreductase - Stiborová, Marie; Dracínská, Helena; Hájková, Jana; Kaderábková, Pavla; Frei, Eva; Schmeiser, Heinz H; Soucek, Pavel; Phillips, David H; Arlt, Volker M (Drug metabolism and disposition: the biological fate of chemicals, 2006)
3-Nitrobenzanthrone (3-NBA), a suspected human carcinogen occurring in diesel exhaust and air pollution, and its human metabolite 3-aminobenzanthrone (3-ABA) were investigated for their ability to induce biotransformation enzymes in rat liver and the influence of such induction on DNA adduct formation by the compounds. Rats were treated (i.p.) with 0.4, 4, or 40 mg/kg body weight 3-NBA or 3-ABA. When hepatic cytosolic fractions from rats treated with 40 mg/kg body weight 3-NBA or 3-ABA were incubated with 3-NBA, DNA adduct formation, measured by 32P-postlabeling analysis, was 10-fold higher in incubations with cytosols from pretreated rats than with controls. The increase in 3-NBA-derived DNA adduct formation corresponded to a dose-dependent increase in protein levels and enzymatic activity of NAD(P)H:quinone oxidoreductase (NQO1). NQO1 is the major enzyme reducing 3-NBA in human and rat livers. Incubations of 3-ABA with hepatic microsomes of rats treated with 3-NBA or 3-ABA (40 mg/kg body weight) led to as much as a 12-fold increase in 3-ABA-derived DNA adduct formation compared with controls. The observed stimulation of DNA adduct formation by both compounds was attributed to their potential to induce protein expression and enzymatic activity of cytochromes P450 1A1 and/or -1A2 (CYP1A1/2), the major enzymes responsible for 3-ABA activation in human and rat livers. Collectively, these results demonstrate for the first time, to our knowledge, that by inducing hepatic NQO1 and CYP1A1/2, both 3-NBA and 3-ABA increase the enzymatic activation of these two compounds to reactive DNA adduct-forming species, thereby enhancing their own genotoxic potential.
Keywords: Microsomes, Liver; benz(a)anthraceny; RNA, Messenger; adukty DNA; Male; Rats, Wistar; látky znečišťující životní prostředí; mužské pohlaví; potkani Wistar; králíci; krysa rodu Rattus; systém (enzymů) cytochromů P-450; NAD(P)H dehydrogenasa (chinon); Animals; lidé; Benz(a)Anthracenes; játra; Carcinogens; Cytochrome P-450 Enzyme System; enzymová indukce; karcinogeny; Humans; zvířata; DNA Adducts; Rats; Rabbits; Environmental Pollutants; Enzyme Induction; Liver; messenger RNA; NAD(P)H Dehydrogenase (Quinone); jaterní mikrozomy